Validation of Thorpe-scale-derived vertical diffusivities against microstructure measurements in the Kerguelen region - Y.-H. Park; J.-H. Lee; I. Durand; C.-S. Hong (Biogeosciences, 2014)
The Thorpe scale is an energy-containing vertical overturning scale of large eddies associated with shear-generated turbulence. This study investigates indirect estimates of vertical diffusivities from the Thorpe scale method in the polar front region east of the Kerguelen Islands based on fine-scale density profiles gathered during the 2011 KEOPS2 (KErguelen Ocean and Plateau compared Study 2) cruise. These diffusivities are validated in comparison with diffusivities estimated from the turbulence dissipation rate directly measured via a TurboMAP (Turbulence ocean Microstructure Acquisition Profiler) microstructure profiler. The results are sensitive to the choice of the diffusivity parameterization and the overturn ratio Ro, and the optimal results have been obtained from the parameterization by Shih et al. (2005) and the Ro = 0.25 criterion, rather than the parameterization by Osborn (1980) and the Ro = 0.2 criterion originally suggested by Gargett and Garner (2008). The Thorpe-scale-derived diffusivities in the KEOPS2 region show a high degree of spatial variability, ranging from a canonical value of O(10−5) m2 s−1 in the Winter Water layer and in the area immediately north of the polar front to a high value of O(10−4) m2 s−1 in the seasonal thermocline between the surface mixed layer and the Winter Water. The latter high diffusivities are found especially over the shallow plateau southeast of the Kerguelen Islands and along the polar front that is attached to the escarpment northeast of the islands. The interaction of strong frontal flow with prominent bottom topography likely causes the observed elevated mixing rates.